A Review of Oil Palm Fruit Ripeness Monitoring Using Microwave Techniques in Malaysia - You, K.Y. (Institute of Physics Publishing, 2020)
Palm oil products are one of the most important sources of economic and export products in Malaysia. Furthermore, now, the evolution of industry 4.0 has begun to take place globally. The development of sensors has played a role in this evolution. In this paper, various microwave sensors used in oil palm monitoring are reviewed. The advantages and disadvantages of each microwave sensor are discussed in detail. However, conventional and optical monitoring methods are also briefly described. Â© Published under licence by IOP Publishing Ltd.